Electronic Circuits for Piezo electric Energy Harvesting and Sensor Array Systems - Gogoi, Niharika (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2023)
This thesis is a comprehensive study of piezoelectric energy harvesting circuits in response to human gait. The main goal of this work is to take advantage of ambient mechanical vibration to power a gait based wearable device integrated in a shoe. Most wearable devices are battery operated,which is followed by unsustainable course of action as the battery life expires. To meet the growing demand of wearable devices with environment friendly approaches, walking is one of the ways. The stress generated from walking has the potential to convert mechanical energy into electrical energy via piezoelectric elements. In this work, the piezoelectric element is used not only as an energy harvester but also as a sensor. We take advantage of the foot-strike to collect gait information and obtain electrical energy simultaneously. This brings a paradigm shift from wrist-based wearables to foot-based wearables. There are several energy harvesting circuits discussed in this work to under stand their response to a gait signal. The circuits studied were standard energy harvesting circuit (SEH), Self-powered Parallel Synchronous Switch Harvesting on Inductor (sp-p-SSHI), Self-powered Synchronous Electric Charge Extraction (sp-SECE), Self-powered Optimized Synchronous Electric Charge Extraction (sp-OSCE) and Full wave Voltage Doubler (VD), and then implemented in the proposed shoe application. Their working principles are assessed and rated against the used case of gait-excited piezoelectric elements. The advantages and disadvantages of these circuit topologies incorporating non-linear techniques are also discussed. Thesystem based-investigation is presented discussing the power consumption of each stage from sensor data collection to data transmission. Athorough analysis of the extent to which piezoelectric elements can contribute to the application with and without battery is presented in this thesis. The role of battery as back-up in simultaneous sensing and energy harvesting is also investigate